(untitled) (International journal of artificial intelligence, 2026)
The rapid development of digital technologies has significantly transformed traditional approaches to language education. Among these innovations, social media platforms have emerged as influential environments for language learning, offering authentic communication, learner autonomy, and interactive engagement. This article explores the role of social media as a language learning environment by analyzing its pedagogical potential, its impact on language skill development, and its contribution to learner motivation. The study also discusses several challenges associated with the use of social media in education and highlights the importance of pedagogical guidance. The findings suggest that when used appropriately, social media can enhance language learning outcomes and support modern learner-centered educational paradigms.